Efficacy of Omalizumab Therapy in an Asthmatic with Low IgE - R, Divya (Case Rep Pulmonol, 2020)
Asthma is one of the most common respiratory diseases encountered in clinical practice. Although the vast majority of asthmatics can be adequately controlled with inhaled steroids and other preventer medications, a small proportion remain uncontrolled. Anti-IgE treatment with omalizumab has been proposed in patients as a preferred approach in step 5 asthma therapy according to GINA guidelines. Although therapy with this molecule is approved for patients with atopic asthma and pretreatment serum IgE levels of 30-1500 only, there have been a few reports of its efficacy in subjects outside this reference IgE range. We report the case of a middle-aged lady with severe corticosteroid-dependent asthma and low serum IgE levels who was successfully treated with 9 months of omalizumab therapy. She gained good asthma control and was tapered off steroid use by the fifth month of therapy with omalizumab. The case report stresses the need for further investigation into expanding the spectrum of omalizumab usage in asthma beyond the current IgE suitability range.